2019
DOI: 10.3390/mi10030176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the TiO2 Nanosolution Concentration on Heat Transfer Enhancement of the Twin Impingement Jet of a Heated Aluminum Plate

Abstract: Here, the researchers carried out an experimental analysis of the effect of the TiO2 nanosolution concentration on the heat transfer of the twin jet impingement on an aluminum plate surface. We used three different heat transfer enhancement processes. We considered the TiO2 nanosolution coat, aluminum plate heat sink, and a twin jet impingement system. We also analyzed several other parameters like the nozzle spacing, nanosolution concentration, and the nozzle-to-plate distance and noted if these parameters co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
0
23
0
3
Order By: Relevance
“…The enhancement of heat transfer is the process of increasing the effectiveness of heat exchanges between two mediums. In industrial applications, jet impingement cooling is widely employed, such as in electronic chip cooling, gas turbine aerofoil cooling and vehicle heat exchangers [1][2][3][4]. Jet impingement offers intensive and local heat transfer, which makes it more adaptable to face heat transfer issues with different geometries and conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement of heat transfer is the process of increasing the effectiveness of heat exchanges between two mediums. In industrial applications, jet impingement cooling is widely employed, such as in electronic chip cooling, gas turbine aerofoil cooling and vehicle heat exchangers [1][2][3][4]. Jet impingement offers intensive and local heat transfer, which makes it more adaptable to face heat transfer issues with different geometries and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This work is representative of the serial publication for our previous papers dealing with the enhancement of heat transfer by using twin impingement jet technique and surface coating [2][3][4] here, we use DOE to analyze the influential parameters studied as the spacing between the nozzles, velocity, concentration of nanosolution coating and nozzle-plate distance, which are considered to be effective parameters for the thermal conductivity and the heat transfer coefficient of TiO 2 nanoparticle. In this article the heat transfer rate could be increased by surface coating with TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Pryazhnikov et al [58] stated that no correlation is found between the particle material and the thermal conductivity of nanofluids through systematic measurements. [59][60][61] found a direct relation between the density of nanoparticles and the thermal conductivity of nanofluids through molecular dynamic simulations. This dependence has been confirmed through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the modification of the twisted tape, the type, size, shape and volume fraction of the nanoparticles are important parameters for heat transfer augmentation [24]. Due to superior thermophysical properties, such as thermal conductivity (k), specific heat (c p ), density (ρ) and viscosity (µ), a nanofluid is a superior substitute as a working fluid.…”
Section: Introductionmentioning
confidence: 99%